Designing and Analysis of T-Shape Microstrip Antenna for the 4G Systems (Global Journal of Computer Science and Technology, 2013)
In this paper, the designing and analysis of T-shape microstrip patch antenna presented. The shape will provide the broad bandwidth which is required for the operation of fourth generation wireless systems. The operating frequency of antenna is 2.5 GHz, the dielectric constant and thickness of the antenna is 4.2, 1.6mm respectively. The simulation results of antenna are done by the help of IE3D Zeland Software (Version 12.0) and MATLAB programming. For the analysis of antenna we used the popular Finite difference time domain method (FDTD). This antenna is fed by a co-axial probe feeding. In this paper, the effects of different types of antenna parameters like return loss, voltage standing wave ratio (VSWR), impedance etc. are also studied.
Keywords: microstrip antenna; 4G system; FDTD; return loss; VSWR